Regional Agreements to Address Climate Change: Scope, Promise, Funding, and Impacts - Iris Butzlaff; Nicole Grunewald; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
There is a large number of regional agreements concerning Greenhouse Gas (GHG) emissions, often linked to other regional integration agreements. The most successful one in making effort in reducing carbon emissions is the Emission Trading System by the European Union (EU ETS). Apart from this exceptional agreement there are many others, which either focus directly on reducing GHG emissions or were embedded in another agreement. There is little known about the origin, the design or funding of those agreements. Therefore, we point to the potential contribution of those agreements in order to reduce GHG emissions and give an overview on the nature of those agreements to evaluate their success. We classify 15 agreements by their subject (technology / R&D, trade and finance) and examine their record to date. We find that the impact on mitigating climate change has been negligible to date, but the potential to contribute to mitigation climate change at the regional level is substantial.
Keywords: Q54; Q58; Q55; 330; Regional cooperation; climate change; mitigation